2006
DOI: 10.1162/jocn.2006.18.7.1045
|View full text |Cite
|
Sign up to set email alerts
|

Brain Basis of Developmental Change in Visuospatial Working Memory

Abstract: Although brain changes associated with the acquisition of cognitive abilities in early childhood involve increasing localized specialization, little is known about the brain changes associated with the refinement of existing cognitive abilities that reach maturity in adolescence. The goal of this study was to investigate developmental changes in functional brain circuitry that support improvements in visuospatial working memory from childhood to adulthood. We tested thirty 8- to 47-year-olds in an oculomotor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
234
5
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(264 citation statements)
references
References 39 publications
22
234
5
3
Order By: Relevance
“…However, similar to our results, other neuroimaging studies have found higher activity in the DLPFC and parietal areas in adolescents compared to children and young adults on VSWM tasks [53] and various executive function tasks [54]. Considering this, it is possible that the difference in functional coupling between G2 and G1 could indicate that adolescents have a more general and non-specific neural activity [55] that requires the integration of more association areas, such as the parietal regions.…”
Section: Discussionsupporting
confidence: 89%
“…However, similar to our results, other neuroimaging studies have found higher activity in the DLPFC and parietal areas in adolescents compared to children and young adults on VSWM tasks [53] and various executive function tasks [54]. Considering this, it is possible that the difference in functional coupling between G2 and G1 could indicate that adolescents have a more general and non-specific neural activity [55] that requires the integration of more association areas, such as the parietal regions.…”
Section: Discussionsupporting
confidence: 89%
“…Children performing visuospatial working memory tasks show the same, but decreased activation pattern compared to adults, especially the dorsolateral prefrontal cortex is less recruited (Klingberg, Forssberg, & Westerberg, 2002;Kwon, Reiss, & Menon, 2002;Nelson et al, 2000;Scherf, Sweeney, & Luna, 2006).…”
Section: Developmental Dyscalculiamentioning
confidence: 88%
“…Functional neuroimaging studies indicate that this developmental progression may also apply to working memory. Children show higher blood oxygenation in additional regions beyond the core working memory areas found in adults (Ciesielski et al., 2006; Crone, Wendelken, Donohue, van Leijenhorst, & Bunge, 2006; Scherf, Sweeney, & Luna, 2006; Vogan et al., 2016). However, differences in the contribution of brain structure with development have not been investigated so far.…”
Section: Discussionmentioning
confidence: 99%